2018
DOI: 10.1038/s41598-018-26993-2
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Upregulation of prefrontal metabotropic glutamate receptor 5 mediates neuropathic pain and negative mood symptoms after spinal nerve injury in rats

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There are contrasting reports on the role of mPFC mGlu5 receptors in pain modulation (27,28,(41)(42)(43)(44). For example, application of mGlu5 receptor antagonists in the ipsilateral prelimbic and infralimbic cortices enhanced neuropathic pain (spared nerve injury) (44), whereas ipsilateral infralimbic application reduced arthritis-induced pain (42) and bilateral application in prelimbic cortex caused antinociception in the spinal nerve ligation model of neuropathic pain (45). Our photopharmacological tools allowed us to establish that pharmacological blockade of mGlu5 receptors in the contralateral mPFC caused antinociception in the CCI model of neuropathic pain, and that prelimbic and infralimbic regions, but not anterior cingulate cortex, play a critical role in mediating systemic mGlu5 NAM antinociception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are contrasting reports on the role of mPFC mGlu5 receptors in pain modulation (27,28,(41)(42)(43)(44). For example, application of mGlu5 receptor antagonists in the ipsilateral prelimbic and infralimbic cortices enhanced neuropathic pain (spared nerve injury) (44), whereas ipsilateral infralimbic application reduced arthritis-induced pain (42) and bilateral application in prelimbic cortex caused antinociception in the spinal nerve ligation model of neuropathic pain (45). Our photopharmacological tools allowed us to establish that pharmacological blockade of mGlu5 receptors in the contralateral mPFC caused antinociception in the CCI model of neuropathic pain, and that prelimbic and infralimbic regions, but not anterior cingulate cortex, play a critical role in mediating systemic mGlu5 NAM antinociception.…”
Section: Discussionmentioning
confidence: 99%
“…2), possibly through projections to cortical regions such as somatosensory and insular cortices, with the latter projecting strongly to the prelimbic cortex (46). Previous studies showed increased mGlu5 receptor expression in the mPFC ipsilateral, but not contralateral, to peripheral nerve injury (45). We used an in vivo method to measure the primary signal transduction mechanism of mGlu5 receptors, i.e., polyphosphoinositide (PI) hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…43 Therefore, future investigations into whether interactions between estrogen and mGlu5 could influence resilience and vulnerability in the SEFL paradigm would be of merit. Second, given mGlu5's involvement in nociception and chronic pain, [44][45][46] it is possible that the painful nature of footshocks is a necessary mediator for a relationship between higher mGlu5 availability and SEFL susceptibility, and that is related to differences in pain processing. This potential confound would fit in with clinical observations suggesting overlapping molecular mechanisms mediating chronic pain syndromes and stress-related psychiatric disorders, including PTSD.…”
Section: Discussionmentioning
confidence: 99%